Opening the Selectivity Pocket in the Human Lysine Deacetylase Sirtuin2 – New Opportunities, New Questions. Issue 12 (21st June 2018) - Robaa, Dina; Monaldi, Daria; Wössner, Nathalie; Kudo, Norio; Rumpf, Tobias; Schiedel, Matthias; Yoshida, Minoru; Jung, Manfred
Abstract: Reversible lysine deacetylation is exerted by both zinc and NAD + ‐dependent deacetylases. It is an important factor in epigenetic regulation and more generally in the posttranslational regulation of protein stability, association and activity. Some of these enzymes can also cleave off fatty acids or dicarboxylic acids from lysines in proteins. The NAD + ‐dependent deacetylases are termed Sirtuins and are implicated in the pathogenesis of different diseases. For the isotype Sirt2 highly selective inhibitors have been identified in the last few years. Many of those Sirt2 selective compounds, like the Sirtuin rearranging ligands (SirReals) discovered in our group, have been shown or are postulated to bind to the so‐called selectivity pocket. This binding site is not observed in crystal structures of the apo‐enzyme but can be opened up by long chain fatty acid substrates respectively suitable inhibitors. Recently, this unique feature of Sirt2 was exploited to provide highly potent and selective tools for the chemical biology of Sirtuins. Here, we shortly review Sirtuin biology, present inhibitors that have either been confirmed or postulated to bind to the selectivity pocket, their applications and an outlook regarding mechanistic investigations. Abstract : Sirtuins are NAD+dependent lysine deacetylases that can also cleave off larger acyl groups and dicarboxylic acids. They are postulated to be targets to treat cancer, neuro‐degeneration and metabolic diseases. Here, we review inhibitors of Sirt2 with a focus on ligands to the so‐called selectivity pocket, such as the SirReals (Sirtuin rearranging ligands).